Genetic testing in patients with retinitis pigmentosa: Features of unsolved cases. (8th May 2019) - Birtel, Johannes; Gliem, Martin; Oishi, Akio; Müller, Philipp L.; Herrmann, Philipp; Holz, Frank G.; Mangold, Elisabeth; Knapp, Michael; Bolz, Hanno J.; Charbel Issa, Peter
Abstract: Importance: Uncommon characteristics in genetically unsolved retinitis pigmentosa (RP) patients may indicate an incorrect clinical diagnosis or as yet unknown genetic causes resulting in specific retinal phenotypes. The diagnostic yield of targeted next‐generation sequencing may be increased by a reasonable preselection of RP‐patients. Background: To systematically evaluate and compare features of genetically solved and unsolved RP‐patients. Design: Retrospective, observational study. Participants: One‐hundred and twelve consecutive RP‐patients who underwent extensive molecular genetic analysis. Methods: Characterization of patients based on multimodal imaging and medical history. Main Outcome Measures: Differences between genetically solved and unsolved RP‐patients. Results: Compared to genetically solved patients (n = 77), genetically unsolved patients (n = 35) more frequently had an age of disease‐onset above 30 years (60% vs 8%; P < 0.0001), showed atypical fundus features (49% vs 8%; P < 0. 0001) and indicators for phenocopies (eg, autoimmune diseases) (17% vs 0%; P < 0. 001). Evidence for a particular inheritance pattern was less common (20% vs 49%; P < 0. 01). The diagnostic yield was 84% (71/85) in patients with first symptoms below 30 years‐of‐age, compared to 69% (77/112) in the overall cohort. The other selection criteria alone or in combination resulted in limited further increase of the diagnostic yield (up to 89%) while excluding considerably more patients (up to 56%) from genetic testing. Conclusions and Relevance: The medical history and retinal phenotype differ between genetically solved and a subgroup of unsolved RP‐patients, which may reflect undetected genotypes or retinal conditions mimicking RP. Patient stratification may inform on the individual likelihood of identifying disease‐causing mutations and may impact patient counselling.